ANALISIS POSISI DAYA SAING CRUDE PALM OIL (CPO) INDONESIA DI ENAM NEGARA IMPORTIR UTAMA - Erizona, Chitra; Napitulu, Dompak; Ningsih, Rozaina (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
CPO is the world main vegetable oil that has the highest production and consumption levels compared to other major vegetable oils. The high level of world consumption of CPO is because in addition to higher production, CPO also has the lowest price compared to other major vegetable oils. Indonesia as the largest CPO exporter in the world makes a major contribution to meeting the world's vegetable oil needs. Indonesia exports CPO to six major importing countries, namely India, the Netherlands, Singapore, Malaysia, Spain and Italy. However, Indonesia's CPO export activities fluctuated to six major importing countries. Indonesia's CPO has the potential to be developed, but also has obstacles in the form of non-tariff barriers in the form of a CPO black campaign from the European Union. The purpose of this study is to analyze the development of Indonesian CPO exports in the six main importing countries, and analyze the competitiveness of Indonesian CPO and countries that are optimistic and potential for the development of Indonesian CPO exports in the six main importing countries. This study uses time series data from 1991 - 2020. The methods used are RCA, EPD, X-Model. The results of the study during the period 1991 - 2020 showed that the average development of Indonesian CPO exports fluctuated and tended to increase in India, Singapore, Malaysia, Spain and Italy, and fluctuated tended to decrease in the Netherlands. Indonesian CPO has strong competitiveness in the six main importing countries, is in a rising star position in the India, Malaysia, Spain and Italy markets, is in a falling star position in the Singapore market and is in a retreat position in the Dutch market. CPO exports have an optimistic market development potential in the Indian, Malaysian, Spanish, Italian markets and a potential market development potential in the Singapore market.